New combinations and other taxonomic changes for the forthcoming ‘Flore des Mascareignes’ Orchidaceae accounts - Hermans, Johan (Universidad de Costa Rica, 2021)
In preparation for the forthcoming orchid accounts of the Flore des Mascareignes lectotypifications are made for Angraecum cadetii, A. cornigerum, A. corrugatum, A. costatum, A. eburneum, A. mauritianum, A, patens, A. pingue, A. tenuifolium, Benthamia erinacea, B. perfecundum, Bulbophyllum commersonii, B. compressum, B. conicum, B. cordemoyi, B. densum, B. pusillum, B. variegatum, Cynorkis arnottioides, C. calcarata, C. calcaripotens, C. cordemoyi, C. falcata, C. fastigiata, C. flexuosatis, C. graminea, C. lilacina, C. nervilabris, C. paradoxa, C. pleiadea, C. purpurascens, C. reticulate, C. squamosa, C. trilinguis, C. variegata, Disperis cordata, Gastrorchis villosa, Habenaria arachnoides, H. lancifolia, H. praealta, H. undulata, Platylepis densiflora, P. margartifera, P. occlusa, Oeceoclades analavelensis and O. pulchra. Neotypifications are made for Angraecum tenuifolium, Benthamia spiraloides, Cynorkis coccinelloides and C. constellata. Clarification is provided of the taxonomy of Angraecum crassifolium, A. tenellum, Benthamia erinacea, Bulbophyllum densum, B. elliotii, B. incurvum, B. pendulum, Cheirostylis boryi, C. gymnochiloides, C. nuda, Cynorkis calcarata, C. coccinelloides, C. falcata, C. flexuosatis, C. squamosa, Habenaria sigillum, Oeceoclades analavelensis, Platylepis densiflora, P. margaritifera and P. occulta. New combinations are made for Benthamia spiraloides, Bulbophyllum elliotii var. latibracteatum, Cheirostylis boryi, Cynorkis aristei and C. flexuosatis. Key words/Palabras clave: Mauritius, new combinations, nuevas combinaciones, new synonyms, nuevos sinónimos, Reunion, Rodrigues, typification, tipificación